Using Existing Bibliographic Resources to Compile Faculty Publication Lists: a Case Study from San Jose State University - Ngoc-Yen Tran; Emily K. Chan (Issues in Science and Technology Librarianship)
With limited campus resources for faculty scholarship, the College of Science (CoS) at San José State University (SJSU) developed scholarly output metrics as a way to add a quantitative component to the distribution of funds, to ensure objectivity, and to reward proven researchers. To support CoS's efforts to identify and quantify science faculty research publications, we compiled a bibliography of science faculty research and scholarship which would be used to develop and formalize baseline research metrics. Using existing and available resources including librarian time, subscribed science databases, and the institution-subscribed reference citation manager, we developed a method by which any library can provide this specialized service.